Stabilized CO2 reforming of CH4 on modified Ni/Al2O3 catalysts via in-situ K2CO3-enabled dynamic coke elimination reaction. (15th August 2021) - Cao, Pengfei; Zhao, Haitao; Adegbite, Stephen; Yang, Bolun; Lester, Edward; Wu, Tao
Graphical abstract: Highlights: K2 CO3 was adopted to improve catalytic performance of Ni/Al2 O3 catalysts. Basicity of the catalyst was raised by K2 CO3 and boosts CO2 reforming of CH4 . K2 CO3 -modified 1.0 K-Ni/Al2 O3 catalyst exhibited a long-term high stability. Coke formation was mitigated via enhanced in-situ consumption of disordered carbon. Transient experiment demonstrated a dynamic K2 CO3 -enabled coke elimination reaction. Abstract: CO2 dry reforming of methane (DRM) is one of the most promising routes for the large-scale utilization of greenhouse gases (CO2 and CH4 ). However, it is still of challenges to develop catalysts that are efficient and cheap but are of high resistivity in coke formation to maintain long-term stability. Herein, K2 CO3 was used as a promoter to enable dynamic coke elimination reaction over the Ni/Al2 O3 for CO2 reforming of CH4 . K2 CO3 -modified Ni/Al2 O3 catalysts were synthesized via a wet co-impregnation method and investigated for DRM. The 1.0 K-Ni/Al2 O3 exhibited the best stability in the test of 96 h on stream at 800 °C. It was found that coke resistance of K2 CO3 modified catalyst was significantly improved, as the coke formation on 1.0 K-Ni/Al2 O3 catalyst was only 1/3 of that on Ni/Al2 O3 catalyst after a long-term test. Characterization results showed that the growth of Ni particles was suppressed because the addition of K2 CO3 enhanced the interaction between Ni and Al2 O3 . Meanwhile, the addition of K2 CO3 raises the basicity of the catalysts, which enhances the adsorption of CO2 on the surface and subsequently facilitates CO2 dry reforming of CH4 . In addition, the transient experiment reveals that K2 CO3 enables a dynamic coke elimination reaction (KCER) via enhancing the catalytic reaction of disordered carbon with CO2, which is considered as a promising low-cost approach to stabilize the performance of the Ni-based catalysts in DRM reaction.